Multiple brain abscesses caused by Nocardia asiatica co-infection with Torque teno virus in an “immunocompetent” patient: a rare case report and literature review - Huang, Weiwei; Ran, Xu; Zhang, Zuoxin; Yang, Lin; Yin, Jinbo; Lv, Shengqing; Liu, Guolong; Pei, Yuchun (Frontiers in Medicine, 2025)
Brain abscess is a suppurative infection of brain tissue caused by one or more pathogens under specific susceptible conditions and is associated with a high clinical fatality rate. Beyond surgical intervention, the identification of pathogens is key to clinical antimicrobial therapy, yet this remains a challenge. Nocardia is a ubiquitous bacterium that typically manifests as an opportunistic infection, primarily affecting immunocompromised individuals. Pulmonary involvement, characterized by suppurative inflammation, commonly occurs following inhalation, with subsequent hematogenous dissemination potentially leading to widespread infection. To our knowledge, central nervous system (CNS) infection by Nocardia asiatica (N. asiatica) resulting in brain abscess has hitherto rarely been reported. We present a rare case of multiple brain abscesses caused by N. asiatica co-infection with Torque teno virus (TTV) in an immunocompetent patient with suspected multiple organ involvement. The patient was admitted to our hospital, presenting with a headache, and imaging revealed brain abscess-like lesions. A robot-assisted stereotactic puncture and drainage were used for abscess removal. N. asiatica and TTV were identified by metagenomic next-generation sequencing (mNGS) of the brain abscess aspirate, with N. asiatica subsequently confirmed by mass spectrometry of the cultured organism. A disseminated Nocardia infection was suspected based on the patient’s skin trauma history, pulmonary inflammatory changes, and imaging findings (liver cysts, subcutaneous nodules). However, etiological confirmation was not obtained prior to his death. While this is not the first reported instance of Nocardia and TTV co-infection in brain abscesses, our case is notable for its occurrence in an immunocompetent patient. This report highlights the significance and value of TTV in the context of brain abscesses and warrants a re-evaluation of Nocardia and TTV co-infection. Given that the diagnosis of intracranial infection depends on the detection of pathogens, we advocate for the routine and early implementation of mNGS testing in patients with brain abscesses. Moreover, systemic nutritional support and immunomodulatory therapies should be considered in the early stage of treatment for complex cases. Earlier diagnosis and treatment in this case might have altered the patient’s outcome.